Genetic and enzymatic analyses of carbohydrate metabolism in Strongylocentrotus purpuratus larvae - Jasper Hildebrand; Meike Stumpp (PANGAEA, 2025)
Strongylocentrotus purpuratus (Stimpson 1857) originally collected in November 2022 from La Jolla, USA (Lat: 32.842674; Long: -117.257767) were held in flow-through tanks which were filled with water from Kiel Fjord adjusted to 31.5 psu in the Christian-Albrechts-Universität zu Kiel at 10 °C. For experimental characterization of carbohydrate digestion between September and November 2023 S. purpuratus larvae were generated by gently shaking adult males and females and held in climate chambers at 15°C and 31.5 psu up to 10 days under two different food conditions. Using RT-qPCR analysis, expression patterns of five glycosidase genes including an amylase, laminarinase, cellulase, xylanase and trehalase were analyzed against the housekeeping gene EF1a. Digestion of starch, laminarin, carboxymethylcellulose, xylan and trehalose were analyzed under different pHs, at different sampling points and under different temperature conditions during and before the reaction using the 3,5-dinitrosalicylic acid (DNS) method (Miller, 1959).